IMPLEMENTASI DATA MINING PADA MENGGUNAKAN METODE FP GROWTH ASSOCIATION RULE PADA DATA TRANSAKSI PENJUALAN - Lwy Indra Agusstewan; Koko Handoko (Computer Science and Industrial Engineering, 2024)
This research focuses on optimizing sales and inventory management for "Gudang Computer" company through the implementation of the FP-Growth method in data mining. Despite operating since October 2020, the company faces challenges in managing sales transactions and inventory. Analysis of transaction data from January to December 2022 resulted in two itemsets, namely TV4G and MWK, meeting the minimum requirements of 20% support and 70% confidence. With these findings, the research demonstrates that if customers purchase TV4G, there is a high likelihood they will also purchase a Mouse Wireless Keyboard. This discovery is expected to assist "Gudang Computer" in operating more efficiently by formulating more targeted sales strategies.